Final Report with Recommendations for Reforming Bulgaria’s Pharmaceutical Sector - World Bank (Washington, DC, 2015)
This report presents a review of current issues in the pharmaceutical sector in Bulgaria, examining drug policy, regulation, pricing, formulary selection, distribution, expenditure, and to the extent possible, patterns of use in Bulgaria. Its recommendations are intended to serve as options for reform, by articulating short and long term strategies for managing pharmaceutical expenditure, improving system sustainability, and driving value for money in Bulgaria, thereby improving efficiency, equity, affordability and ultimately, access to prescription medicines. Although small, the Bulgarian pharmaceutical market is showing strong growth. Medicines comprise not only a disproportionate share of health care expenditure (38 percent of total health expenditure, compared with an EU average of around 25 percent), the burden of out of pocket (OOP) costs is also excessive, possibly as high as 81 percent of total pharmaceutical expenditure. Of perhaps greatest concern is that rapid expenditure growth is taking place without obvious improvements in health outcomes, and at the expense of population equity. Bulgaria does not yet have an integrated national medicines policy, and the pharmaceutical sector is characterized by various highly prescriptive and at times, arguably inconsistent policy levers. While the regulatory framework has been largely brought into line with current EU standards, existing mechanisms for listing, pricing and subsidizing medicines are not ensuring adequate value for money for the National Health Insurance Fund (NHIF), and are contributing to inefficiencies in the health sector. Current pharmaceutical policy settings appear focused on limiting NHIF outlays rather than prioritizing access and affordability, and afford little financial protection to patients.